The legal basis for regulating refugees’ right to work: a study within the framework of international agreements and Iraqi legislation - Ibrahim Mohsen Jabr, Lect. (lark, 2025)
In light of the increase in the number of refugees worldwide in recent decades due to wars and other causes of displacement, it becomes essential to examine the legal framework governing refugees’ right to work from two main perspectives: international conventions on one hand, and national legislation on the other. This study explores the extent to which national laws align with international obligations. The right to work for refugees is not merely a right to employment, but a practical manifestation of the principle of non-discrimination as established by international agreements. This right constitutes not only a legal obligation, but also a humanitarian duty imposed by the Universal Declaration of Human Rights. The principle of non-discrimination ultimately leads to the economic empowerment of refugees and their integration into society, while also enhancing the host countries’ commitment to the principles of justice and equality. Therefore, it is both a moral and legal responsibility borne by states.